Abundance and Distribution, Growth Pattern, Sex Ratio and Gonadosomatic Index (GSI) of Liza falcipinnis (Valenciennes, 1836) from Ojo Axis of Badagry Creeks, Lagos, Nigeria - O.A., Adeboyejo; E.O., Clarke; A.M., Hammed; O.O., Whenu; J.P., Abayomi; O.M., Olarewaju (Sustainable Marine Structures, 2021)
A study on seasonal abundance, morphometric and meristic data, growth pattern, condition factor, sex ratio and gonadosomatic index of Liza falcipinnis (Valenciennes, 1836) from the Ojo axis of Badagry creek, Nigeria was conducted from May 2019 to March 2020. A total of 1012 species were randomly selected, having 499 females and 513 males. The length frequency analysis and length-weight relationships (LWR) were determined. Sex ratio was determined by Chi-square analysis. The results showed that morphometric data are: 0.5 - 2.5 mm for ED, 2.1 - 12 mm for HL, 1.7 - 8.1 mm for HD, 2.5 - 11.7 for BD, 2.6 - 233.3 mm for TL and 9.23 - 1006 g for BW for the combined sexes. The slope (b) shows an allometric growth pattern. The intercept ‘a’ and slope ‘b’ of the LWR (LogW = a + bLogL) were Log W=15.39+ 0.34 LogL (r= 0.54) for combined sexes, Log W= 12.49+ 0.02 log L (r= 0.38) for males and Log W= 18.23+ 0.01 log L (r=0.16) for females.The length frequency distribution indicated that species were dominated by two year classes (Ages 1 and 2). Condition factors were generally low. The values ranged between 0.68 - 0.85 for combined sexes. The gonadosomatic index for female was highest in August, 2019 (17.77%) with Mean±SD of 2.88±0.75; which indicated the peak of spawning period in the study area.Sex ratio difference was significant (P<0.05). Sexual differences were significant; the females are phenotypically larger than the male. ER